The Mechanics of Speed: A Systematic Literature Review on Athletic Sprint Techniques - Rumini; Adi S; Donny Wira Yudha Kusuma (Physical Education Theory and Methodology)
Objectives. This study aimed to collect and analyze findings from research on athletic sprinting techniques through a biomechanics approach to provide an in-depth understanding of effective technique and biomechanical factors that influence sprint performance.